Isolation and Selection of Radiation Resistant Fungi from Mamuju High Natural Radiation Soil for Uranium and Thorium Bioremediation - Robifahmi, N.; Laksmana, R. I.; Pratama, A. A.; Kusuma, A. T.; Tjiptosumirat, T.; Tuasikal, B. J.; Nugraha, E. D.; Rijal, M. S.; Febrian, V. A.; Yusup, M.; Futy, W.; Mujiyanto, A.; Sugoro, I. (National Research and Innovation Agency, 2026)
Microorganisms from high natural radiation environments hold potential as bioremediation agents for radioactive waste. In this study, isolation and selection of fungi from Mamuju high natural radiation soil was done for radioactive bioremediation. The methods included fungal isolation from soil samples, radiosensitivity tests, sensitivity tests to uranium and thorium, and absorption tests under gamma radiation (100 Gy hour-1). Results revealed three fungal isolates with high growth ratios and resistance to gamma radiation: Talaromyces flavus (A3), Gongronella butleri (A4), and Aspergillus sp. (F1). Isolates A3 and A4 survived up to 2 kGy, while F1 endured up to 8 kGy. At 24 hours, A3 absorbed uranium at 96% with a biomass of 0.73 g and thorium at 84% with 0.98 g biomass. A4 achieved the highest uranium absorption of 97% (biomass 4.11 g) and thorium absorption of 100% (biomass 0.74 g). F1 demonstrated 96% uranium absorption (biomass 1.29 g) and 87% thorium absorption (biomass 2.17 g). These isolates exhibited significant potential for bioremediation of uranium and thorium-contaminated environments, showing unique adaptations to high radiation conditions and effective radioactive metal uptake.